Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, dan Pengalaman Menggunakan Sistem E-Filling Pada Penggunaan Sistem E-SPTPD - Jayatenaya, I Gde Oka; Jati, Ketut (E-Jurnal Akuntansi; Vol 23 No 3 (2018), 2018)
ABSTRACT The use of technology makes it easy to do the job. This study aims to determine the use of e-SPTPD system by taxpayers as a means of tax reporting, as measured by usability perception, ease of perception, and experience using e-filling system. The use of e-SPTPD system is the acceptance of e-SPTPD system by the taxpayer as a means of tax reporting. This research was conducted at Badung District Revenue Office. The number of samples studied were 96 taxpayers of e-SPTPD users. The method of determining samples using convenience sampling is the technique of determining samples by chance, ie anyone who accidentally / incidentally met with the researcher can be used as a sample, when viewed by someone who happens to be met as a data source. Data collection was done through questionnaires. The analysis technique used is multiple linear regression analysis. Based on the analysis, it can be concluded that the perception of usability, ease of perception, and experience of using e-filling system have a positive effect on the use of e-SPTPD system.   Keywords: usability, ease, experience, system usage